Some tarsonemid mites (Acari: Tarsonemidae) from the Brazilian "Cerrado" vegetation, with descriptions of three new species - Lofego, A.c.; Ochoa, R.; Moraes, G.j. (Zootaxa, 2005)
Seven tarsonemid species were found in leaf samples from the "Cerrado" vegetation in the State of São Paulo in southeastern Brazil. Mensuration data of four species, Daidalotarsonemus tesselatus De Leon, Tarsonemus bilobatus Suski, Tarsonemus confusus Ewing and T. waitei Banks are provided. Three new species, Daidalotarsonemus folisetae Lofego & Ochoa, Metatarsonemus megasolenidii Lofego & Ochoa and Tarsonemus longisetae Lofego & Ochoa are described. Food habits of D. tesselatus are discussed.